Preconception Prebiotic and Sitagliptin Treatment in Obese Rats Affects Pregnancy Outcomes and Offspring Microbiota, Adiposity, and Glycemia - Dennison, Carol A.; Eslinger, Amanda J.; Reimer, Raylene A. (Frontiers in Endocrinology, 2017)
Maternal obesity is associated with increased risk of pregnancy complications and greater risk of obesity in offspring but studies designed to examine preconception weight loss are limited. The objective of this study was to determine if a combined dietary [oligofructose (OFS)] and pharmacological [sitagliptin] preconception intervention could mitigate poor pregnancy outcomes associated with maternal obesity and improve offspring metabolic health and gut microbiota composition. Diet-induced obese female Sprague-Dawley rats were randomized to 1 of 4 intervention groups for 8 weeks: 1) Obese-Control (consumed control diet during intervention); 2) Obese-OFS (10% OFS diet); 3) Obese-S (sitagliptin drug); 4) Obese-OFS+S (combination treatment). Two reference groups were also included: 5) Obese-HFS (untreated obese consumed high fat/sucrose diet throughout study); 6) Lean-Control (lean reference group that were never obese and consumed control diet throughout). Offspring consumed control diet until 11 weeks of age followed by HFS diet until 17 weeks of age. The Obese-OFS+S rats lost weight during the intervention phase while the OFS and S treatments attenuated weight gain compared to Obese-HFS (p < 0.05). Gestational weight gain was lowest in Obese-OFS+S rats and highest in Obese-HFS rats (p < 0.05). Pre-pregnancy intervention did not affect reproductive parameters but did affect pregnancy outcomes including litter size. Male Obese-OFS offspring had significantly lower percent body fat than Obese-HFS at 17 weeks. Female Obese-S and Obese-OFS offspring had significantly lower fasting glucose at 17 weeks compared to Obese-Control and Obese-HFS. Clostridium cluster XI was higher in Obese-HFS and Obese-S dams at birth compared to all other groups. Dams with an adverse pregnancy outcome had significantly lower (p = 0.035) Lactobacillus spp. compared to dams with normal or small litters. At weaning, male offspring of Obese-HFS had higher levels of Methanobrevibacter than all other groups except Obese-S and female Obese-HFS offspring had higher Enterobacteriaceae compared to all other groups. At 11 and 17 weeks of age, Bacteroides/Prevotella spp. was significantly lower in male and female offspring of Obese-HFS dams compared to all other groups except Obese-OFS+S. Modest weight loss induced with a diet-drug combination did not affect maternal fecundity but did have sex-specific effects on offspring.